Health services : policy and systems for the therapists - Sandstrom, Robert W., 1957-; Lohman, Helene; Bramble, James D. (New York : Routledge, 2025)
This new edition of Health Services: Policy and Systems for the Therapists provides a comprehensive introduction to the structure and organization of the U.S. health care system, and the application of private and government insurance programs across a range of clinical practice areas. The book provides an essential introduction to the latest policy developments, exploring issues such as access, cost, quality, licensure, informed consent, and medical liability. The book provides, too, detailed guidance on practical issues, including communication with managed care organizations and government claims reviewers, compliance and fraud/abuse prevention, and the completion of key documentation. This new edition has also been updated not only with the latest policy changes, but with new material on population health, value-based health care, and telehealth. This is the ideal text to enable both students and practitioners across allied health disciplines to feel confident and assured working within the U.S. health care system.
Public policy and therapists -- Access and cost of health care -- Quality of health care -- Population health, public health, and value-based health care -- Public policies advancing community inclusion -- Fundamentals of insurance -- Private insurance and therapy practice -- Medicare -- Medicaid, military/veterans medical insurance, and Indian Health Service -- The acute medical care system -- The post acute health care system -- The role of therapy services in educational systems -- Effecting policy change : therapist as advocate.
Keywords: Medical policy; MEDICAL / Allied Health Services / Occupational Therapy